2014
DOI: 10.1371/journal.ppat.1003923
|View full text |Cite
|
Sign up to set email alerts
|

Lundep, a Sand Fly Salivary Endonuclease Increases Leishmania Parasite Survival in Neutrophils and Inhibits XIIa Contact Activation in Human Plasma

Abstract: Neutrophils are the host's first line of defense against infections, and their extracellular traps (NET) were recently shown to kill Leishmania parasites. Here we report a NET-destroying molecule (Lundep) from the salivary glands of Lutzomyia longipalpis. Previous analysis of the sialotranscriptome of Lu. longipalpis showed the potential presence of an endonuclease. Indeed, not only was the cloned cDNA (Lundep) shown to encode a highly active ss- and dsDNAse, but also the same activity was demonstrated to be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 36 publications
2
79
0
3
Order By: Relevance
“…Following this event, there is rapid accumulation of neutrophils [20] and it has been shown that the co-inoculated salivary molecules can modulate neutrophil function [33,34]. Herein, we confirmed neutrophil infiltration to the site of L .…”
Section: Discussionsupporting
confidence: 73%
“…Following this event, there is rapid accumulation of neutrophils [20] and it has been shown that the co-inoculated salivary molecules can modulate neutrophil function [33,34]. Herein, we confirmed neutrophil infiltration to the site of L .…”
Section: Discussionsupporting
confidence: 73%
“…L. infantum (HYG) was derived from L. infantum (MHOM/ES/92/LLM-320; isoenzyme typed MON-1) (27), provided by Diane MacMahon-Pratt (Yale School of Public Health, New Haven, CT). Wild-type L. infantum promastigotes were transfected with the RFP/Hyg expression cassette and selected on hygromycin B-containing agar plates as described (36). The integration of the expression cassette into the 18S rRNA locus in selected drug-resistant clones was verified by PCR.…”
Section: Methodsmentioning
confidence: 99%
“…Polyclonal antibodies against recombinant Aegyptin (7) were raised in rabbits by Spring Valley Laboratories as described in ref. 37.…”
Section: Methodsmentioning
confidence: 99%